Analisis Dan Perancangan Sistem Informasi Penjualan Produk Kesehatan Pada PT. ABC - T. Husain (ULTIMA InfoSys, 2017)
The object of research is PT. ABC. The company was founded in 2003, running a business as a distributor of sales products, such as multivitamins and supplements. Currently, PT. ABC is still not yet used a computerized sales information system between one process with another process. PT. ABC has difficulty data costumer archiving, finding data and the process of report presenting takes a relatively long time. The purpose of research is to analyzing the current information system and make an sales information system based application with adding sales return system which has complements fit up the product database. This application is expected to provide accurate information about the process of sales product health. The method used is qualitative research method through the study of literature, interview and observation. Analysis of current systems using the entity-relationship model (ERM). The design of system using the PHP language programming with a MySQL database. The results obtained from this study is a making a computerized database as of can make report with quickly, accurately and informative. Keywords – computerized database; design of sales information system; MySQL database, PHP language program.co